2016
DOI: 10.1016/j.jvs.2015.08.067
|View full text |Cite
|
Sign up to set email alerts
|

Degree of contralateral carotid stenosis improves preoperative risk stratification of patients with asymptomatic ipsilateral carotid stenosis

Abstract: Our study identifies a high contralateral degree of ICAS as an independent predictor of preoperative ipsilateral TIA and stroke in patients with ipsilateral high-grade ICAS. Therefore, such patients might rather benefit from elective carotid surgery and intensive postoperative medical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
3
0
1
Order By: Relevance
“…This mechanism is the main cause of a negative outcome. In this respect, several studies have shown that chronic hypoperfusion can be asymptomatic even over a long period of time with good contralateral compensation, increased over time, by collateral flow ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This mechanism is the main cause of a negative outcome. In this respect, several studies have shown that chronic hypoperfusion can be asymptomatic even over a long period of time with good contralateral compensation, increased over time, by collateral flow ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Higher mortality in AIS patients with a CCS > 50% and an ipsilateral patent carotid artery has been observed ( 3 , 4 ). The presence of significant CCS in patients with severe ICS was found to be an independent risk factor for acute cerebral vascular impairment with a 3-fold higher risk of TIA or stroke ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“… 13 Thus, it is important to evaluate the degree of preoperative carotid artery stenosis to accurately assess the risk and predict the need for CEA. 1 , 6 , 14 Therefore, standardizing cut-off values for parameters is of great significance for patient screening and evaluating clinical treatment. However, in the early 1990s, some studies 7 9 reported that diagnostic criteria assessed using CDU overestimated the stenosis degree for bilateral carotid artery stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…Basic и соавт. подтвердили, что степень контралатерального стеноза имеет прямую корреляцию с риском периоперационного инсульта [18]. A. Gupta и соавт.…”
Section: Discussionunclassified